Analisis Genetik dan Seleksi Segregan Transgresif pada Populasi F2 Sorgum Hasil Persilangan B69 × Numbu dan B69 × Kawali - Maryono, Marina Yuniawati; ,, Trikoesoemaningtyas; Wirnas, Desta; Human, dan Soeranto (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2019)
The genetic analysis and selection of transgressive segregants on agronomic characters are required in a sorghumbreeding program for obtaining high proportion homozygosity rapidly in the early generations. This study aimed to obtainthe information on the performance of agronomic characters, estimate genes’ action, broad-sense heritability, coefficient ofgenetic variability, and select transgressive segregant on F2 population of sorghum based on grain yield. The research wasconducted from July 2014 until October 2014 in Dramaga, Bogor. About 300 and 150 individuals F2 populations of B69 ×Numbu and B69 × Kawali, respectively, were used as genetic materials. The results showed that plant height and paniclelength of B69 × Numbu and B69 × Kawali populations were controlled by many genes with additive gene action. The grainyield and grain yield per panicle were controlled by many genes with additive gene action and complementary epistasis,had high heritability, and large coefficients of genetic variability. The transgressive segregant selection had selected 14individuals of B69 × Numbu and 134 individuals of B69 × Kawali populations based on grain yield per panicle.